Unsaturated lipids modulating the interaction of the antileishmanial isolinderanolide E with models of cellular membranes - Rosa, Matheus Elias; Conserva, Geanne A. Alves; Passero, Luiz Felipe D. [UNESP]; Lago, João Henrique G.; Caseli, Luciano (Elsevier, 2022)
The present work evaluated the antiprotozoal activity of isolinderanolide E, isolated from the Brazilian plant Nectandra oppositifolia, against promastigote forms of Leishmania (Leishmania) amazonensis. The compound exhibited an EC50 value of 20.3 μM, similar to the positive control miltefosine (IC50 of 19.4 μM), and reduced toxicity to macrophages (CC50 > 200 μM). Based on these results, Langmuir monolayers of two unsaturated lipids: 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) and 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE), were employed as a model of mammalian and parasite membranes, respectively, to study the interaction of isolinderanolide E at a molecular level. The films were characterized with tensiometry (surface pressure-area isotherms and surface pressure-time curves), infrared spectroscopy, and Brewster angle microscopy (BAM). This compound changed the profile of the isotherms leading to fluid DOPC and DOPE monolayers, which were not able to attain rigid states even with compression. Infrared spectroscopy showed that the bioactive compound decreases the trans/gauche ratio conformers related to the molecular conformational disorder. BAM showed the formation of specific aggregates upon drug incorporation. In conclusion, isolinderanolide E changes the thermodynamic, mechanical, structural, and morphological characteristics of the monolayer of these unsaturated lipids, which may be essential to understand the action at the molecular level bioactives in biointerfaces.
Keywords: Air-water interface; DOPC; DOPE; Isolinderanolide E; Leishmania (L.) amazonensis; Monolayers